Does Climatic Seasonality of the Caatinga Influence the Composition of the Free lists of Medicinal Plants? A Case Study - Ernani Machado de Freitas Lins Neto; Silvana Vieira dos Santos; Washington Soares Ferreira Júnior (Ethnobiology Letters, 2021)
The free list is a key data collection tool in ethnobotanical studies. For this reason, it is currently receiving a great deal of attention regarding possible methodological limitations. To this end, we aim to investigate the influence of climatic seasonality of the Caatinga ecosystem on the composition of free lists of medicinal plants provided by people from a rural community located in the northeast region of Brazil. People were asked the same trigger question (which medicinal plants do you know?), during the rainy and dry seasons. Comparing the plant lists described during both periods (68 plants), respondent salience in the rainy period was significantly higher than the dry period. However, similarities can be observed between the two lists, especially with respect to their composition and the continued importance of hortelã (Mentha sp.) and alecrim (Lippia sp.), which maintained prominent positions during the rainy and dry seasons. The general analysis of the free lists revealed that there were no significant differences due to temporality, especially in relation to plants with a higher salience value. Since these plants are found mainly in homegardens, it is possible to deduce that the daily conduct of activities in these environments is stimulating and keeping plants in homegardens active in people’s memory. However, much still needs to be investigated about the free list technique in ethnobotanical data collection, especially with regard to the influence of seasonality on stimulating seasonal diseases.